The development and transcriptome regulation of the secondary trunk of Ginkgo biloba L. - Cao, Zhong-yun; Su, Li-ning; Zhang, Qian; Zhang, Xin-yue; Kang, Xiao-jing; Li, Xin-hui; Sun, Li-min (Frontiers in Plant Science, 2023)
Secondary trunk Ginkgo biloba is one of the specific germplasms of G. biloba. In this study, paraffin sectioning, high-performance liquid chromatography and transcriptome sequencing technology were used to study the development of the secondary trunk of G. biloba from the morphological, physiological and molecular levels. The results showed that the secondary trunk of G. biloba originated from the latent buds in the stem cortex at the junction of the root and stem of the main trunk. The development process of secondary trunk was divided into 4 periods: the dormancy period of the secondary trunk buds, the differentiation period, the formation period of transport tissue, and the budding period. Transcriptome sequencing was performed by comparing the germination period and elongation growth period of the secondary trunk with the normal parts of the same period where no secondary trunks occurred. Differential genes involved in phytohormone signal transduction, phenylpropane biosynthesis, phenylalanine metabolism, glycolysis and other pathways can regulate not only the inhibition of early dormant buds but also the later development of the secondary trunk. Genes related to IAA synthesis are upregulated and indole-3-acetic acid content is increased, leading to the up-regulated expression of IAA intracellular vector genes. The IAA response gene (SAUR) receives and responds to IAA signals to promote the development of the secondary trunk. Through the enrichment of differential genes and functional annotations, a key regulatory pathway map for the occurrence of the secondary trunk of G. biloba was sorted out.